2022
DOI: 10.1099/ijsem.0.005418
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas bonasiae sp. nov. and Xanthomonas youngii sp. nov., isolated from crown gall tissues

Abstract: The genus Xanthomonas contains a set of diverse bacterial strains, most of which are known for their pathogenicity on annual crops and fruit trees causing economically important plant diseases. Recently, five Xanthomonas strains were isolated from Agrobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Using a 95% cut-off value as an ANI species delimiter (Goris et al 2007; Richter and Rosselló-Móra 2009), SLC-5 strain CFBP 8443 was found to be the only representative for this novel species. The SLC-6 strain CFBP 8444 and its clone NCPPB 2983 in the UK strain collection represent a sister species of X. bonasiae (Mafakheri et al 2022). Three nearby strains in the dendrogram, GW, SI, and SS, which were isolated as candidate biocontrol agents from the microbiome of perennial ryegrass (Lolium perenne), were found to be phylogenetically close to the species X. bonasiae (Li et al 2020).…”
mentioning
confidence: 99%
“…Using a 95% cut-off value as an ANI species delimiter (Goris et al 2007; Richter and Rosselló-Móra 2009), SLC-5 strain CFBP 8443 was found to be the only representative for this novel species. The SLC-6 strain CFBP 8444 and its clone NCPPB 2983 in the UK strain collection represent a sister species of X. bonasiae (Mafakheri et al 2022). Three nearby strains in the dendrogram, GW, SI, and SS, which were isolated as candidate biocontrol agents from the microbiome of perennial ryegrass (Lolium perenne), were found to be phylogenetically close to the species X. bonasiae (Li et al 2020).…”
mentioning
confidence: 99%
“…Besides the known X. translucens collection, a set of non-X. translucens members within the clade I of Xanthomonas were also included in the assays (Mafakheri et al 2022). Non-xanthomonad bacterial pathogens of small grains cereals i.e.…”
Section: Validation Of the Primers For Specificity And Sensitivitymentioning
confidence: 99%
“…This analysis involved 75 genome sequences and confirmed the taxonomic position of the three SLC strains within clade 1 (Figure 1; Supplemental Using a 95% cut-off value as an ANI species delimiter (Goris et al 2007; Richter & Rosselló-Móra 2009), SLC-5 strain CFBP 8443 was found to be the only representative for this novel species. The SLC-6 strain CFBP 8444 and its clone NCPPB 2983 in the UK strain collection represent a sister species of X. bonasiae (Mafakheri et al 2022). Three nearby strains in the dendrogram, GW, SI, and SS, which were isolated as candidate biocontrol agents from the microbiome of perennial ryegrass (Lolium perenne), were found to be phylogenetically close to the species X. bonasiae (Li et al 2020).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Thanks to increased genome sequencing efforts, the number of Xanthomonas genome sequences has increased tremendously in recent years, including strains of scientifically and/or economically relevant species and pathovars (Mansfield et al 2012). But also understudied non-model organisms have been systematically sequenced, thus correcting taxonomically mis-assigned strains and leading to description of novel species (Vicente et al 2017; López et al 2018; Martins et al 2020; Bansal et al 2021; Dia et al 2021; Mafakheri et al 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation